Beyond Conventional Insider Trading: Indonesia’s Shadow Trading Dilemma - Tjahjadi, Bryan Gadrian; Teeja, Nathania Wiandra (Anthology: Inside Intellectual Property Rights, 2025)
Shadow trading represents an emerging challenge in financial regulation, involving the use of material nonpublic information (MNPI) by corporate insiders to trade in the securities of companies other than their own. Traditionally falling outside the scope of the classical insider trading theory—which is centered on fiduciary duty—shadow trading remained largely unregulated and unprosecuted. This changed in 2024 with the landmark U.S. case SEC v. Panuwat, where the Securities and Exchange Commission (SEC) successfully prosecuted the first shadow trading case. The SEC extended the Misappropriation Theory by introducing the novel “Market Connection” element, thereby establishing a legal foundation for prosecuting shadow trading as a form of insider trading. This paper critically examines the implications of this legal development for Indonesia, where the existing Capital Market Law, enacted in 1995, has not kept pace with evolving financial crimes. The law’s continued reliance on outdated fiduciary-based frameworks creates significant regulatory gaps, particularly in dealing with indirect or unconventional trading schemes. Employing a normative juridical method and comparative analysis, this study evaluates the capacity of Indonesia’s current legal framework to address shadow trading and explores how regulatory strategies and enforcement mechanisms adopted by the U.S. SEC may inform much-needed reforms to strengthen Indonesia’s capital market oversight and investor protection.